Comparison of two treatment protocols in children with unilateral complete cleft lip and palate: Tridimensional evaluation of the maxillary dental arch. Issue 9 (September 2016) - Jorge, Paula Karine; Gnoinski, Wanda; Vaz Laskos, Karine; Felício Carvalho Carrara, Cleide; Gamba Garib, Daniela; Okada Ozawa, Terumi; Andrade Moreira Machado, Maria Aparecida; Pinelli Valarelli, Fabrício; Oliveira, Thais Marchini
Abstract: Objective: The aim of this study was to evaluate the dimensional alterations of the maxillary dental arches after lip repair in children with unilateral complete cleft lip and palate of two different protocols. Material and methods: The sample was composed of 94 digital models and divided in two groups: Group I – 23 children, (protocol 1) – with presurgical orthopedic intervention: Hotz plate; Group II – 24 children, (protocol 2) – without presurgical orthopedic intervention. The three dimensional images of the maxillary arch were obtained before lip repair (stage 1) and at approximately 1 year of age (stage 2). Interstages changes for each group were evaluated using dependent t test and Wilcoxon test, and in the intergroup were used independent t test, and Mann–Whitney test. Results: The comparison of the dimensional alterations of dental arches between the two protocols exhibited differences: in the stage 1, the intercanine was smaller in Group II; in the stage 2, the anterior cleft width, the intercanine and the anteroposterior cleft were smaller in Group II. Conclusion: The results reported here suggest that the use of infant orthopedic plate as applied in protocol 1 may favor correct arch form establishment in infants with unilateral complete cleft lip and palate.